Xyela longula , Dalman 1819 - Blank, Stephan M.; Shinohara, Akihiko; Altenhofer, Ewald (Zenodo, 2013)
Xyela longula Dalman, 1819 AUSTRIA: Lower Austria, Wiener Neustadt W 20 km, Hohe Wand [16.00°E 47.82°N], 24.4.1948, leg. Fulmek, 1♂, NMW [identified as X. helvetica by Blank 2002, fig. 7]; North Tyrol, Zirler Berg, Martinswand [11.20°E 47.32°N], 22.3.1980, leg. E. Heiss, 3♀ 3♂, DEI; 26.3.1980, leg. W. Schedl, 1♀, EJC. CZECHIAN REPUBLIC: Vrané nad Vltavou [14.38°E 49.94°N], 12.4.1970, leg. J. Strejček, 1♂, MKC. FINLAND: Hame, Hämeenlinna, Käikälä [24.45°E 61.00°N], 2.5.1982, leg. V. Vikberg, 1♀ 1♂, MZHF; Hame, P. - Pirkkala [23.58°E 61.47°N], 6.6.1910, leg. Th. Grönblom, 1♀, MZHF; Hame, Turenki [24.63°E 60.91°N], 30.6.2005, leg. V. Vikberg, 1♀ 2♂, DEI [2 specimens used for barcoding: DEI-GISHym 15643–15644]; Finland, Hame, Turenki, Konttila [24.66°E 60.90°N], 30.6.2005, leg. V. Vikberg, 39 larvae from Pinus sylvestris , DEI [1 specimen used for barcoding: DEI-GISHym 15657]; Uusimaa, Nurmijärvi [24.80°E 60.47°N], 18.5.1980, leg. M. Koponen, 1♂, MZHF. FRANCE: Ile-de-France, Seine-et-Marne, F. de Fontainebleau [2.70°E 48.41°N], 12.5.1935, leg. A. Seyrig, 1♀, MNHN; Auvergne, Tence [4.28°E 45.12°N], 10.4.1927, leg. H. Maneval, 1♂, MNHN (tentative identification). GERMANY: Bavaria, Fränkischer Jura [11.50°E 49.33°N], 1.5.1940, leg. E. Enslin, 1♀, MKC; Bavaria, Fürth [10.97°E 48.48°N], 20.4.1915, leg. E. Enslin, 1♀, ZSM; same data, 12.4.1920, 1♂, MKC; Bavaria, Steigerwald [10.50°E 49.80°N], 20.4.1939, leg. E. Enslin, 1♂, MKC; Bavaria, Vilstal, Poxau 2 km N [12.55°E 48.56°N], 25.3.2007, leg. A.D. Liston, 1♂, DEI; Brandenburg, Carls. [=Karlsruhe], Gyr. [= Kyritz] [12.40°E 52.95°N], leg. F.W. Konow, 2♀, DEI, SMFD; Brandenburg, Fürstenberg in Mecklenburg [13.17°E 53.18°N], leg. F.W. Konow, 1♂, ZMUC; same data, 17.4.1889, 1♀, HNHM; same data, 10.4.1891, 1♀, ZMUC; Mecklenburg-Vorpommern, T. [= Teschendorf in Mecklenburg, in coll. Konow] [13.37°E 53.45°N], 23.4.1898, leg. F.W. Konow, 1♂, DEI; same data, 28.3.1903, 1♂, DEI; Mecklenburg-Vorpommern, Waren / Müritz [12.68°E 53.52°N], 9.4.1931, 1♂, ZMUH; North Rhine-Westphalia, Crefeld [= Krefeld] [6.58°E 51.33°N], 4.1913, 1♀, MKC; Sachsen-Anhalt, Halle an der Saale [11.97°E 51.48°N], 1♀, MKC; Sachsen-Anhalt, Halle an der Saale, Dölauer Heide [11.88°E 51.51°N], 19.4.1914, leg. Schlüter, 1♀, MKC. NETHERLANDS: Noordwijk [4.43°E 52.25°N], April, leg. S.C. Snellen van Vollenhoven, 1♀, ZMAN. RUSSIA: Moskovskaya Oblast, Losinyi ostrov [37.82°E 55.85°N], 6.5.1984, leg. A.P. Rasnitsyn, 1♀, ZMUM; Sankt Peterburg Oblast, Dep. Maruya, Novoladozhsk. u. [= uezd, = area], Petrogradskoy guberniy [= province] [31.85°E 60.08°N], 29.6.1917, leg. W. Barovskiy, 1♀, ZIN; Sankt Peterburg Oblast, Luga [29.85°E 58.74°N], 15.4.– 15.5.1914, leg. A. Gutbir, 1♀, ZIN; Sankt Peterburg Oblast, Vyritsa [30.35°E 59.42°N], 2.5.1977, leg. A. Zinovjev, 1♀, ZIN. SWEDEN: Gävleborgs Län, Gästrikland [16.66°E 60.68°N], leg. C.H. Boheman, 2♀ 1♂, NHRS; Jämtlands Län, Jämtland [14.18°E 63.13°N], leg. C.H. Boheman, 1♀ 1♂, NHRS; Jönköpings Län, Småland, Hultsjö [14.70°E 57.32°N], 4.5.1927, leg. S. Pontin, 1♀, MZLU; Kopparbergs Län, Dalarna, Rättvik, Mun. samh:t [15.13°E 60.89°N], 11.5.1977, leg. T. Tjeder, 1♂, MZLU; Kopparbergs Län, Småland, Hornberga, Trambroan till Nyavägen [14.59°E 61.20°N], 26.4.1926, 1♀, NHRS; Lpl. [= Lappland] [20.17°E 61.20°N], leg. C.G. Thomson, 1♀, MZLU [lectotype of X. piliserra , Thomson 1871]; Vestrogothia [= Skaraborgs län or Älvborgs län], 1♀, UUZM [lectotype of X. longula , Dalman 1819]; Västerbottens Län, Lyksele Lappmark, Sorsele [17.54°E 65.54°N], 17.5.1921, leg. D. Gaunitz, 1♂, MZLU. SWITZERLAND: Vaud, Peney [6.55°E 46.80°N], 16.4.1886, 1♀, MHNG. AMBIGUOUS: [no data], 2♀, MZLU; [no data], 1 specimen, MZLU [additional label: “ Xyela erichsoni är sunno liktblatten varietet af longula ”]; [no data], 15.4.1895, 1♀, MMBC. : Published as part of Blank, Stephan M., Shinohara, Akihiko & Altenhofer, Ewald, 2013, The Eurasian species of Xyela (Hymenoptera, Xyelidae): taxonomy, host plants and distribution , pp. 1-106 in Zootaxa 3629 (1) on pages 101-102, DOI: 10.11646/zootaxa.3629.1.1, http://zenodo.org/record/5261330